SIMULASI CFD PADA DIFFUSER AUGMENTED WIND TURBINE (DAWT) : EFEK BENTUK INLET DAN PANJANG DIFUSER TERHADAP DISTRIBUSI KECEPATAN ANGIN DI EXIT DIFUSER [CFD SIMULATION IN DIFFUSER AUGMENTED WIND TURBINE (DAWT): EFFECT OF INLET SHAPE AND DIFFUSER LENGTH ON WIND SPEED DISTRIBUTION AT DIFFUSER EXIT] - Sulistyo Atmadi; Ahmad Jamaludin Fitroh (Jurnal Teknologi Dirgantara, 2012)
The objective of the research is to obtain a lighter diffuser design. It is done by modifications previously designed diffuser on the shape and length of its inlet. Thus the study analyze the effect of modified inlet and diffuser length on the distribution of wind speeds at the nozzle exit. Analysis was performed using a CFD-based software. Modifications was made to the diffuser inlet and exit diameter each-amounting to 4 and 2 m. Modified inlet can improve performance by 1.4%; meanwhile the wind angle of 60º, the performance was reduced by 2.45%, due to the separation. Shortening the length diffuser can reduce the velocity distribution in the exit, maximum of occurs at length of 1 m at 4.6%. Therefore it is recommended that optimum diffuser length is 2 m. Key words: Wind turbine, Diffuser, CFD